Mental Health Difficulties of Incarcerated Women: The Influence of Childhood and Adulthood Victimization. Issue 3 (2nd July 2020) - Casey, Rachel C.; Bentley, Kia J.; McDonald, Shelby E.
Abstract: With the aim of identifying avenues for targeted implementation of trauma-informed care in correctional contexts, this study engaged in a secondary data analysis to examine comorbidity patterns in the mental health difficulties of incarcerated women. Latent class analysis was conducted using nine indicators of mental health, and indicated the sample (N = 2553) was best represented by four patterns of mental health functioning: serious mental illness (8.7%); mood and drug use disorders (30.3%); substance use only (11.7%); and no/low mental health concerns (49.4%). Multinomial logistic regression indicated that sexual and physical victimization in childhood were important in distinguishing between the classes. These findings support the increased use of trauma-informed approaches to mental health treatment for incarcerated women.